Incorporation of nomina of higher-ranked taxa into the International Code of Zoological Nomenclature: some basic questions - Dubois, Alain (Zootaxa, 2006)
Several proposals have recently been published regarding the possible incorporation of nomenclature of higher taxa (class-series nomina) into the International Code of Zoological Nomenclature. Some basic questions related to this problem are discussed here. Introducing standard endings for the nomina of these taxa would probably be a kind of hara-kiri for LinnaeanStricklandian nomenclature of higher taxa: it would upset nomenclatural stability by introducing many new nomina and abandoning most of the nomina that have been in constant use in zoology for a long time to other nomenclatural systems alternative to the Code. Nomina of higher taxa should rather all belong in a single nominal-series, the class-series. They should not be submitted to a Rule of Coordination (except for identical taxa of different ranks), and their allocation to taxa should not be made through extensional or intensional definitions, but through ostension with a special system combining onomatophores (the conucleogenera) and onomatostases (the alienogenera). This system provides clear, unambiguous, stringent and universal Rules for the nomination of higher taxa in the future, compatible with all taxonomic systems including “phylogenetic” ones, while respecting the freedom of taxonomic thought and actions, as well as the tradition long attached to nomina of higher taxa in zoology.